Immunocytes do not mediate food intake and the causal relationship with allergic rhinitis: a comprehensive Mendelian randomization - Zhang, Zhi-qiang; Li, Jing-yang; Bao, You-wei; Song, Yu-Qi; Song, Dong-xu; Wang, Cheng; Zhu, Xin-hua (Frontiers in Nutrition, 2024)
Observational studies indicate a correlation between food intake and allergic rhinitis. The potential interplay between the immune system and allergic rhinitis might contribute causally to both food intake and allergic rhinitis, providing promising therapeutic avenues. However, elucidating the causal relationship and immune-mediated mechanisms between food intake and allergic rhinitis remains a pending task. Methods: We utilized a two-sample Mendelian randomization (MR) methodology to explore the causal relationship between food intake and allergic rhinitis. Furthermore, we investigated the potential causal relationship of immune cell signals with allergic rhinitis, as well as the potential causal relationship between food intake and immune cell signals. Moreover, employing both two-step Mendelian randomization and multivariable Mendelian randomization, we delved into the mediating role of immune cell signals in the causal relationship between food intake and allergic rhinitis. Leveraging publicly accessible genetic datasets, our analysis encompassed 903 traits, comprising 171 food intake features, 731 immune cell features, and one trait related to allergic rhinitis. Result: We found causal relationships between seven types of food intake and allergic rhinitis, as well as between 30 immune cell phenotypes and allergic rhinitis. Furthermore, our two-step Mendelian randomization analysis and multivariable Mendelian randomization analysis indicate that immune cells do not mediate the causal relationship between food intake and allergic rhinitis. Conclusion: To the best of our knowledge, we are the first to incorporate a large-scale dataset integrating immune cell features, food intake features, and allergic rhinitis into Mendelian randomization analysis. Our research findings indicate that there are causal relationships between six types of food intake and allergic rhinitis, as well as between 30 immune cell phenotypes and allergic rhinitis. Additionally, immune cells do not mediate these relationships.